La ricerca nelle scuole di dottorato in Italia. Dottorandi e docenti a confronto: il Seminario SIRD - Luciano Galliani (Journal of Educational, Cultural and Psychological Studies, 2010)
Research in Graduate Schools in Italy. Doctoral Students and Teachers Exchange Views: the SIRD Seminar